A diagnosis of the artisanal production process of alpaca fiber yarn in Puno, Peru - Díaz-Garay, Bertha (2021)
This research aimed to find out the current state of the artisanal production process of alpaca fiber yarn in the department of Puno, Peru. To that end, a descriptive and exploratory study was carried out, having as unit of analysis the alpaqueros (alpaca breeders), artisans, medium-scale producers and some textile managers. A documentary research was conducted to obtain qualitative and quantitative data on the production of alpaca yarn. In 2019, field research was carried out to collect the data directly from the alpaquero communities, thus obtaining information on the methods of the production process of alpaca fiber yarn. It was concluded that the artisanal production of alpaca yarn mainly maintains a handmade process. However, small machines such as opening machines and spinning machines, which consist of simple mechanical devices, have been incorporated in the production process to reduce the fiber production time and to improve the yarn quality.